DINAMIKA PENGATURAN PERJANJIAN BAGI HASIL TANAH PERTANIAN DARI HUKUM ADAT KEPADA UNDANG-UNDANG - SANIAH . (LP2MTBM MAKARIOZ, 2022)
Transactions for agricultural land yields are initially regulated by local customary law where the agreement is executed. The implementation of the agreement is only based on the agreement. In this condition, the regulations based on the law do not protect the interests of the cultivicators. After the promulgation of law no. 2 of 1960 and its implementing regulations promulgated in Presiden Instruction no. 13 of 1980, the profit sharing agreement must be stated in writing. Additional institutions that are always attached to profit sharing agreements according to customary law, such as sromo and mesi have been removed. Thus, with the dynamics of the arrangement of profit sharing agreements, the rights of the cultivators are more protected.